(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
The building called Life Star standing on single point support of vertex of the cone holding sphere on the flat round base of the cone. Life star is a star shaped building structure inherited from the shapes of sun and star and nature too as life will exist in an artificial star. Life star building for is made up of two shapes in sphere and cones. a solid geometric figure generated by the revolution of a semicircle about its diameter a round body whose surface is at all points equidistant from the center. The surface of such a figure a spherical surface. This paper presents the detailed about the Life star Concept.